SPATIOTEMPORAL CHARACTERISTICS OF EXTREME RAINFALL EVENTS OVER JAVA ISLAND, INDONESIA - Supari Supari; Sudibyakto Sudibyakto; Janneke Ettema; Edvin Aldrian (Faculty of Geography, Universitas Gadjah Mada, 2012)
The patterns and trends of extreme daily rainfall within period of 1981 – 2010 have beenanalyzed for Java Island, Indonesia particularly East Java Province. A set of extreme indicesrecommended by WMO were calculated using high quality data from 84 rain stations toexpress the frequency and intensity of those events. The spatial patterns was identified bymapping climatological mean of indices while temporal trends was assessed using the nonparametricMann-Kendal test. The study found that the spatial pattern of extreme rainfallevents over East Java Province is generally characterized by low frequency and intensity inthe coastal area, and high frequency and intensity in the mountainous area. The dominantfinding from trend assessment is not-significant trend. However, the consistently significanttrend was observed in some districts. Rain stations in District of Ponorogo, Ngawi,Bojonegoro, Gresik and Sumenep showed significant negative trend for almost all indiceswhereas significant positive trend was found in District of Surabaya and Pasuruan.